Diasteroselective multi-component assemblies from dynamic covalent imine condensation and metal-coordination chemistry: mechanism and narcissistic stereochemistry self-sorting. Issue 35 (29th May 2018) - Badetti, Elena; Carmo dos Santos, Nadia Alessandra; Scaramuzzo, Francesca A.; Bravin, Carlo; Wurst, Klaus; Licini, Giulia; Zonta, Cristiano
Abstract : Enantio narcissistic self-assembly is observed in a multi-metallic structure used as stereodynamic probe for CD measurements. Abstract : Self-assembly of a modified tris(2-pyridylmethyl)amine TPMA ligand, zinc(ii ) or cobalt(ii ) ions, and amino acids have been used effectively as stereo dynamic optical probes for the determination of the enantiomeric excess of free amino acids either using Electronic or Vibrational Circular Dichroism (CD and VCD). Herein, we report the mechanistic and stereochemical study of the self-assembly process which reveals a complex equilibrium in solution where even small variations in the experimental conditions can profoundly affect the final products of the reaction. In particular, variation on the metal stoichiometry switch give rises to an entirely enantio narcissistic self-assembly of the structure.